2010
DOI: 10.1038/ismej.2010.58
|View full text |Cite
|
Sign up to set email alerts
|

Soil bacterial and fungal communities across a pH gradient in an arable soil

Abstract: Soils collected across a long-term liming experiment (pH 4.0-8.3), in which variation in factors other than pH have been minimized, were used to investigate the direct influence of pH on the abundance and composition of the two major soil microbial taxa, fungi and bacteria. We hypothesized that bacterial communities would be more strongly influenced by pH than fungal communities. To determine the relative abundance of bacteria and fungi, we used quantitative PCR (qPCR), and to analyze the composition and diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

265
1,848
62
28

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 3,342 publications
(2,203 citation statements)
references
References 50 publications
265
1,848
62
28
Order By: Relevance
“…For example, the cool temperate forest soils with rich SOM and better development were closely associated with the total bacteria and gram‐negative bacteria group, similar to the findings of other studies (Balser & Firestone, 2005; Kramer & Gleixner, 2008; You et al., 2014). The subtropical soils, being more acidic, were strongly associated with actino‐bacteria—a metabolically versatile group of microorganisms that degrade lignin and cellulose (Rousk et al., 2010). Our previous studies well established that biotic and environmental factors control soil C transformation and turnover by shaping the soil microbial structure (Sun et al., 2016; You et al., 2014, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the cool temperate forest soils with rich SOM and better development were closely associated with the total bacteria and gram‐negative bacteria group, similar to the findings of other studies (Balser & Firestone, 2005; Kramer & Gleixner, 2008; You et al., 2014). The subtropical soils, being more acidic, were strongly associated with actino‐bacteria—a metabolically versatile group of microorganisms that degrade lignin and cellulose (Rousk et al., 2010). Our previous studies well established that biotic and environmental factors control soil C transformation and turnover by shaping the soil microbial structure (Sun et al., 2016; You et al., 2014, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In opposition, the decrease of soil pH was reported in agricultural soils dedicated to lettuce, livestock fodder and orange production irrigated with wastewater for more than 15, 20 and 40 years, respectively (Table 4). Although the effects on soil microbiota due to the abovementioned pH variations were not explored in those studies, this parameter seems to be an important determinant of the richness (number of different species) and diversity (variety of organ-isms) of soil bacterial communities (Fierer and Jackson, 2006;Lauber et al, 2009;Rousk et al, 2010). In a comprehensive study comparing soil bacterial communities from distinct ecosystems it was observed that communities of sites with identical pH values share similar indices of bacterial diversity and richness, irrespective of other factors such as climate conditions or edaphic properties (Fierer and Jackson, 2006).…”
Section: Physicochemical Soil Properties Versus Soil Microbiotamentioning
confidence: 99%
“…PyOM produced from different materials under different conditions can result in a wide range of pH values (Enders et al, 2012), and in this study, PyOM additions significantly increased soil pH (Supplementary Figure 17), albeit by less than a full pH unit. Soil pH is strongly correlated with community composition (Lauber et al, 2009;Rousk et al, 2010). In particular, the aptly named phylum Acidobacteria has been shown to be especially sensitive to pH shifts, although its subgroups show variable responses to acidity: subgroups 1, 2 and 3 have been shown to increase at lower pHs, whereas subgroups 4, 5, 6, 7 and 17 have been shown to increase at higher pHs (Rousk et al, 2010;Bartram et al, 2013).…”
Section: Pyom Effects On the Soil Bacterial Communitymentioning
confidence: 99%
“…Soil pH is strongly correlated with community composition (Lauber et al, 2009;Rousk et al, 2010). In particular, the aptly named phylum Acidobacteria has been shown to be especially sensitive to pH shifts, although its subgroups show variable responses to acidity: subgroups 1, 2 and 3 have been shown to increase at lower pHs, whereas subgroups 4, 5, 6, 7 and 17 have been shown to increase at higher pHs (Rousk et al, 2010;Bartram et al, 2013). Both Bartram et al (2013) and Rousk et al (2010) characterized soils from long-term (50+ and 100+ years, respectively) liming trials, so it is not possible to predict from those studies the expected timescale of a soil bacterial community response to pH changes.…”
Section: Pyom Effects On the Soil Bacterial Communitymentioning
confidence: 99%